On securing the generational challenge of urban resilience. Issue 3 (May 2015) - Coaffee, Jon; Clarke, Jonathan
Abstract : The concept of resilience has become increasingly important to our understanding of contemporary planning policy and practice. Resilience offers a new and increasingly relevant set of ideas, tools and approaches to help understand the complexities of an increasingly urbanised world and in the provision of safety and security of communities against an array of perceived hazards and threats. In this paper we reflect upon the emergence and usage of resilience thinking in urban planning, highlighting how traditional planning practices might be seen as maladaptive in response to risk and create impediments to the actual use of resilience principles by planners. To conclude this paper we illuminate the urgent requirement to better connect theories of resilience to their actual practice in order to close the implementation gap in urban resilience praxis.